Gampsocleis sedakovii subsp. sedakovii - Storozhenko, Sergey Yu. (Zenodo, 2023)
Gampsocleis sedakovii sedakovii (Fischer von Waldheim, 1846) Gampsocleis sedakovii sedakovii : Ermakova, 2011: 19; Ermakova et al. , 2016: 126. Remarks. This subspecies is widely distributed throughout Siberia and adjacent regions (Storozhenko, 2004). A single specimen has been recorded from the mountain steppe in the Yana Plataeu (middle basin of the Yana River, Northeast Yakutia). Published as part of Storozhenko, Sergey Yu., 2023, Orthoptera of Northeast Asia and Northwest America, pp. 564-578 in Zootaxa 5264 (4) on page 566, DOI:10.11646/zootaxa.5264.4.6, http://zenodo.org/record/7837186